Lippincott manual of nursing practice. - Nettina, Sandra M. (Lippincott Williams & Wilkins, 2010)
This classic reference book is the one source every nurse needs for essential nursing knowledge. Designed in an easy-to-read format, this guide covers a wide range of disorders and patient problems in all basic areas of nursing, including, medical-surgical, pediatric, maternity, and psychiatric.